A GERT Network Model for input-output optimization of general aviation industry chain based on value flow. (February 2023) - Zhang, Na; Ou, Meng; Liu, Bin; Liu, Jian
Highlights: Propose a new GERT model based on value flow maximization considering resource limits. Analytic algorithm and determination method of relevant parameters are studied. Better solve the problem of effective allocation of aviation industry chain resources. Achieve the common goal of maximizing the overall value. Analyze the random variable probability density function by maximum entropy criterion. Abstract: In view of resources, demand-supply mismatch in the process of building a general aviation industry chain, considering input-output optimization, this paper designs a Graphical Evaluation and Review Technique (GERT) model based on value flow maximization under limited resource constraints by defining the general aviation industry chain GERT network basic unit with such resources flow as logistics, information flow, and cash flow. Through the value transfer GERT network model, this paper, based on the input and output statistics, studies and analyzes how to rationally allocate resources to maximize the value flow of logistics, information flow, and cash flow in the design process of general aviation industry chain under the constraint of limited resources. The result shows that the general aviation industry chain's input-output optimization GERT network model is based on value flow by contrasting the chain's value appreciation under the scenario of whether there is optimal resource allocation when limited resources are constrained. This study established a new research methodology for resource allocation by demonstrating that the optimum resource allocation exists and can be achieved by coordinating logistics, information flow, and capital flow in the general aviation sector's value generation and resource flow.